Research on the Chinese returned millennial employees’ attitudes toward the effectiveness and future development of the incentive mechanism in Chinese enterprises from the perspective of human resource management - Zou, Yi (2020)
Purpose- More and more Chinese millennials who have overseas study experience have taken key positions in Chinese enterprises. However, there is little research about the unique characteristics of this specific population and their attitudes toward the motivation mechanism in Chinese enterprises. Therefore, the purpose of this paper is to define the characteristics of Chinese returned millennials and investigate the Chinese returned millennial employees’ attitudes toward the effectiveness and future development of the incentive mechanism in Chinese enterprises from the perspective of human resource management. Design/methodology/approach- Valid quantitative data were collected from 186 Chinese millennials who had overseas studying experience. Findings- Chinese returned millennial employees were aware that enterprises are using different incentives to motivate them, but they were generally negative about their work status and incentives. Therefore, Chinese enterprises still have room to improve their current incentives mechanism. Enterprises should develop multi-level incentive mechanisms and focus more on material motivators. Research limitations/implications- Future research on the effectiveness of motivation mechanisms on Chinese returned millennial employees can be extended to a wider geographical range and larger simple size. A qualitative strategy and technique, such as case study and interview, could be used for deeper investigation. Originality/value- In addition to extending the current literature on the characteristics of Chinese returned millennials, this study also investigated the effectiveness of current motivation mechanisms which target Chinese returned millennials as well as the millennials’ attitudes toward the various incentives in Chinese enterprises. Keywords- Chinese returned millennials, attitudes, motivation mechanism, Chinese enterprises, human resource management Paper type- Dissertation